Minimally invasive laparoscopic and robotic anterior lumbar interbody fusion: a systematic review and future directions - Isabella Decker; Mohamad Bakhaidar; Summer Shabana; Meriem Boukhiam; Sabino Zani; Muhammad Abd-El-Barr (BMC Surgery)
Abstract Introduction Anterior Lumbar Interbody Fusion (ALIF) is a commonly performed spine surgery procedure used to treat lumbar conditions such as degenerative disc disease, spondylolisthesis, and spinal deformities. Traditionally, it has been performed using open and mini-open surgical techniques. Recently, however, laparoscopic and robotic-assisted ALIF have gained attention for their potential benefits, including shorter recovery times, fewer complications, and improved patient outcomes. However, the safety, effectiveness, and long-term outcomes of these newer techniques remain to be fully compared to conventional methods. Methods The systematic review was conducted in accordance with the PRISMA 2020 guidelines. MEDLINE and Cochrane databases were searched for studies on laparoscopic and robotic approaches to the anterior spine, with a focus on ALIF. Article selection and data extraction were independently conducted by two reviewers. Studies involving animal models, non-ALIF robotic techniques, or non-English publications were excluded. Results A total of 650 articles were initially identified. After screening, a full-text review was conducted on 80 articles, of which 48 studies met the inclusion criteria: 42 focused on laparoscopic ALIF (L-ALIF) and 6 on robotic-assisted ALIF (R-ALIF). Laparoscopic ALIF achieved similar outcomes to mini-open methods, offering limited consistent benefits while presenting challenges such as a steep learning curve and a higher risk of retrograde ejaculation. Data on robotic-assisted ALIF, though limited, indicated improved precision and a reduced rate of intraoperative complications. However, high costs, logistical challenges, and the lack of substantial long-term outcome data remain significant barriers to the broader adoption of this technique in spine surgery. Conclusion L-ALIF and R-ALIF present promising minimally invasive alternatives to mini-open ALIF approaches. L-ALIF yields outcomes similar to mini-open techniques, though its technical demands warrant careful consideration. R-ALIF shows potential for improved precision and reduced complications, but logistical and financial constraints limit its wider adoption. Future studies should focus on multicenter prospective trials, alongside efforts to reduce costs and enhance training, to refine the role of these techniques in optimizing patient outcomes.